Exploring the evidence : commemoration, administration and the economy - Clark, Linda, 1946- (Fifteenth century, 2014)
"Of necessity, historians of the late Middle Ages have to rely on an eclectic mix of sources, ranging from the few remaining medieval buildings, monuments, illuminated manuscripts and miscellaneous artefacts, to a substantial but often uncatalogued body of documentary material, much of it born of the medieval administrator's penchant for record keeping. Exploring this evidence requires skills in lateral thinking and interpretation - qualities which are manifested in this volume. Employing the copious legal records kept by the English Crown, one essay reveals the thinking behind exceptions to pardons sold by successive kings, while another, using clerical taxation returns, adds colour to contemporary criticism of friars for betraying their vows of poverty. Case studies of the registers of two hospitals, one in London the other in Canterbury, lead to insights into the relations of their administrators with civic and spiritual authorities. A textual dissection of the epilogues in William Caxton's early printed works focuses on the universal desire for commemoration. Other essays about royal livery collars and the English coinage are nourished by material remains, and where contemporary records fail to survive, as in the listing of burials in parish churches, notes kept by sixteenth-century heralds and antiquaries provide clues for novel identifications. The book-ends are exemplars of the historian's craft: the one, taking as its starting point the will of Ralph, Lord Cromwell, explores in forensic detail how his executors coped with their enormous task in a time of civil war; the other, by examining research into the economy of fifteenth-century England undertaken since the 1880s, provides an over-view which scholars of the period will find invaluable. Contributors: Martin Allen, Christopher Dyer, David Harry, Susanne Jenks, Maureen Jurkowski, Simon Payling, Euan Roger, Christian Steer, Sheila Sweetinburgh, Matthew Ward."--Page 4 of cover.